Determinan Kepuasan Pengguna Sistem Coretax dan Dampaknya terhadap Kepatuhan Wajib Pajak pada Generasi Z dan Milenial - Meiliana Astri; Syarbini Ikhsan; Haryono Haryono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
Digital transformation in tax administration has become a strategic agenda for the Indonesian government, marked by the launch of CoreTax as an integrated tax administration system. This study examines the effects of system, service, and information quality on CoreTax user satisfaction, and the effect of user satisfaction on taxpayer compliance among Generation Z and Millennials in Pontianak. Its novelty lies in focusing on CoreTax as a newly launched system and on digital-native taxpayer segments that remain underexplored in prior literature. Using a quantitative causal approach, data from 177 respondents selected through purposive sampling were analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that system, service, and information quality each have a positive and significant effect on user satisfaction. User satisfaction is also found to positively and significantly affect taxpayer compliance. Future research is encouraged to broaden the taxpayer sample and incorporate additional factors such as perceived ease of use, institutional trust, and tax awareness.